Patch testing in suspected face allergic contact dermatitis to cosmetics in a tertiary hospital: a prevalence study on causative cosmetic allergens / Dr. Raja Noor Azimah Raja Zulkifly - Raja Zulkifly, Raja Noor Azimah (Faculty of Medicine, 2023)
Background/Objective: Cosmetic contact dermatitis (CD) has been an increasing concern as many new products are introduced. The face is the most exposed to cosmetics which results in face dermatitis. We aimed to determine the prevalence of positive reactions to cosmetic allergens from standard and cosmetic patch test series among suspected face allergic contact dermatitis to cosmetic patients who attended HUiTM Dermatology Clinic. Methods: A cross-sectional study was performed between June to December 2022 involving 49 patients aged between 18-30 years old. All patients underwent standard and cosmetic series patch testing. The results were according to the International Contact Dermatitis Research Group (ICDRG) protocol. Results: Our study cohort compressed 93.8% patch test positivity rate either to standard, cosmetic or both series. There was a high prevalence (n=49, 85.4%) of positivity to cosmetic series alone. The most prevalent clinical presentation among suspected face CD was erythema (n=49, 25.2%) which cheek being the most frequently affected site (n=45, 40.5%). Facial and hair care products (n=45, 22.6% and 20.1 %) respectively were the most suspected product causing allergic CD. Cosmetic patch test positivity was highest with preservative allergens (68%) predominantly to thimerosal (n=41, 8.1 %) followed by sodium metabisulfite (n=4 l, 4.5%). Antioxidant allergens that probable cause CD were gallate mix (n=4 l, 7.2%) and dodecyl gallate (n=41, 5.4%). The most positive standard allergens were nickel(l l) sulfate hexahydrate (n=32, 15.1 %), textile dye mix (n=32, 15.1 %), caine mix III and fragrance mix (n=32, 6.32%) respectively. Conclusion: The most cosmetic related allergens identified were from preservative (68%), fragrance (45%), emulsifier (11 %) and antioxidant (7%) groups. National multicentre registry data is required to support national cosmetic product legislation and to enhance public education.